The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2478/geoca-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between skarn ore deposits and magmatic activity in the Ahar region, Western Alborz, NW Iran

Abstract: Paleocene to Oligocene tectonic processes in northwest Iran resulted in extensive I-type calc-alkaline and alkaline magmatic activity in the Ahar region. Numerous skarn deposits formed in the contact between Upper Cretaceous impure carbonate rocks and Oligocene-Miocene plutonic rocks. This study presents new field observations of skarns in the western Alborz range and is based on geochemistry of igneous rocks, mineralogy of the important skarn deposits, and electron microprobe analyses of skarn minerals. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies on mafic-intermediate rocks have been suggested that the parental mafic gabbroic magmas were generated from a spinel-peridotite source via 5-20% degrees of fractional melting at a depth of ∼52 km (Mollai et al, 2014). According to Mollai et al (2014), fractionation modeling involving the major elements reveals that the diorites are the products of fractional crystallization of gabbroic rocks. The produced dioritic melts ponded at a level of neutral buoyancy probably located at the crust-mantle boundary and would have transferred both heat and mass to the overlying lower crust.…”
Section: Proposed Magma Mingling/mixing Scenariomentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on mafic-intermediate rocks have been suggested that the parental mafic gabbroic magmas were generated from a spinel-peridotite source via 5-20% degrees of fractional melting at a depth of ∼52 km (Mollai et al, 2014). According to Mollai et al (2014), fractionation modeling involving the major elements reveals that the diorites are the products of fractional crystallization of gabbroic rocks. The produced dioritic melts ponded at a level of neutral buoyancy probably located at the crust-mantle boundary and would have transferred both heat and mass to the overlying lower crust.…”
Section: Proposed Magma Mingling/mixing Scenariomentioning
confidence: 97%
“…Trace element ratio modeling indicates that the gabbroic magmas were generated from a spinelperidotite source via 5-20% degrees of fractional melting at 52 Km depth (Mollai et al, 2014).…”
Section: Petrogenesis Of Mafic-intermediate Rocksmentioning
confidence: 99%
“…The mixed rocks (granodiorites) cover an area of approximately 20 km 2 and are exposed at the contact of granitic and maficintermediate stocks which all of them are emplaced into Precambrian metamorphic complex (Khodabandeh et al 2002;Ghaffari 2008;Ghaffari et al 2013). Marble, recrystallized limestone and a skarn zone have developed at the contact of mafic-intermediate rocks with the limestone which is a common phenomenon in North West of Iran (Mollaei et al 2009;Mollai et al 2014). The Quaternary basaltic rocks which occurred after Late Miocene calc-alkaline magmatism are the last phase of magmatism activity (Dabiri et al 2011).…”
Section: Geological Settingmentioning
confidence: 97%
“…The lat ter, as the name im plies, are the skarns that con tain min er ali sa tion, and are formed as a re sult of in fil tra tion of flu ids de rived from ig ne ous in tru sions. In the Ahar re gion the pro cesses that lead to the for ma tion of skarn de pos its in clude three stages as follows: (1) Em place ment of plutonic magma which leads to isochemical con tact meta mor phism (cal cite, pyroxene, plagioclase); (2) prograde metasomatic skarn for ma tion as the pluton cools and an ore fluid de vel ops, (epidote, tremolite/actinolite, chlorite) and; (3) ret ro grade al ter ation of ear lier formed min eral as sem blages, lead ing to the for ma tion of hydrosilicate min er als along with ore de po si tion (Mollai et al, 2014). In gen eral, skarns are zoned from endoskarns in the caus ative pluton, to prox i mal gar net and dis tal pyroxene, a pat tern which also in di cates the over all ox i da tion state of the skarn sys tem (Meinert et al, 2005).…”
Section: Skarn Depositsmentioning
confidence: 99%